UTILIZING CHATGPT FOR ANALYZING ARABIC TEXTS IN THE STUDY OF NAHWU (ARABIC GRAMMAR) - Muhammad Ibnu Tamam; Muhamad Muzaki Kurnia Ilahi; Zahirotu Cholilah; R. Taufiqurrochman; Umi Machmudah (Kitaba, 2024)
This research is based on the rampant use of Artificial Intelligence in learning in this digital era. There is no exception in learning Arabic. Various Artificial Intelligence can be used to perform certain tasks. Among them is ChatGPT. This study aims to test the accuracy of ChatGPT in analyzing Arabic Qowa’id from one of the texts in the book Qira’at ar-Rasyidah. This research is a literature study with a qualitative descriptive method. The techniques used in collecting data are documentation and content analysis. The results of this study show that there is an accuracy between the results of Qowa’id detection by ChatGPT and the Qowa’id Theory proposed by experts. Of all the words that have been analyzed, 99% show suitability. However, as an Artificial Intelligence, of course, mistakes are still found even if it is only 1%. So from this research, it is hoped that readers can understand that ChatGPT can indeed be used in learning Arabic, one of which is to identify Qowa’id, However, a deeper correction is still needed. In addition, the researcher invited academics to conduct similar research to explore the potential use of other Artificial Intelligence that can be used in learning.